O rio Paraguai como tema gerador de ações em educação ambiental escolar no Município de Cáceres - Mato Grosso - Lima, Aguinel Messias de (Universidade Federal de São Carlos, 2009)
The present study was developed at two schools of the municipality of Cáceres, area of the Alto Pantanal , in the West of the State of Mato Grosso. The research focuses the River Paraguay as an indicative theme of action in environmental education (EA) through the school to the sustainability of the river. The aim is to comprehend the river as an analysis and reflection element to the elaboration of a proposal of school educational intervention that contributes to the planning process of the educational actions to the sustainability of the river Paraguay. The participants of the research are teachers and students from the State high school Onze de Março (EEOM) and teachers/students from the first cycle of the fundamental teaching (I IV) from the Municipal School Jardim Paraíso (EMJP). The investigation occurred in three stages. In the first stage of data collecting, it was used the technique of questionnaire application, and it was answered by 23 teachers and 86 students from EEOM and by 0 9 teachers and 24 students from EMJP. As for the second stage other questionnaire was applied to 19 teachers and 41 students from EEOM and to 05 teachers and 12 students from EMJP in three strategies: A (before the trip to the river), B (exhibition of landscapes, like pictures) and C (trip to the river). In the third collecting, through actions made at the schools of the research, the results point out that the teachers from EEOM have diverse academic formation and the ones from EMJP are graduated in Pedagogy and History. The practice of EA focuses the ecological content of the atmosphere. In the EEOM it is approached in the disciplines of Geography, Chemistry and Biology and by projects in both schools. In general, the potentialities of the river most noticed by the participants are: the water, the biodiversity, besides, the fish; whereas, the main environmental problem noticed is pollution (solid residues and sanitary exhaustion). However, there was a difference of environmental perception of the river in the three strategies of data collecting. In the strategy B of data collecting, the landscape no. 13 of the Fishing Festival (FIP) was the most valued. The strategy B " (landscapes) and C allowed larger perceptive field (space) of the elements of the landscape/river when compared to A . However, in the strategy C , it was noticed the socio-environmental problem of the occupation of the riverbanks. In general, the aesthetic and affective values of the river were the most valued and they relate to the nonmaterial satisfaction of the participants. The third stage, developed at the school, it contributed to the (re)construction of nature and environment concepts, and EA for comprehension of the educational practices of the environmental dimension. The tendency of EA is conservationist/resourcist of environment as a place to live and a system of naturalistic nature. The results of the research pointed out to the need of continuous formation in EA. There is need of a critical/transformational practice of school EA, using the river as an educational potential to the local environmental sustainability.
Keywords: Rios; Paraguai, Rio (MT); Educação ambiental; Percepção ambiental; CIENCIAS BIOLOGICAS::ECOLOGIA